Genitourinary tumors. Issue 5 (10th September 2022) - Herr, Harry; Sogani, Pramod; Eastham, James
Abstract: Memorial Sloan Kettering Cancer Center (MSK) has made many notable contributions to the scientific understanding and care of patients with common urologic cancers. Many of the advances represented paradigm shifts in management and established new standards of care. This review highlights the surgical procedures and treatment strategies originated and pioneered by urologic surgeons and colleagues at MSK during the past 50 years.